2013
DOI: 10.1200/jco.2012.48.5938
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Entecavir Prophylaxis for Rituximab-Associated Hepatitis B Virus Reactivation in Patients With Lymphoma and Resolved Hepatitis B

Abstract: Undetectable HBV viral load before chemotherapy did not confer reactivation-free status. Antiviral prophylaxis can potentially prevent rituximab-associated HBV reactivation in patients with lymphoma and resolved hepatitis B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
277
2
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(295 citation statements)
references
References 31 publications
10
277
2
5
Order By: Relevance
“…[210][211][212] Prophylaxis with ETV or TDF or TAF can be also considered in HBsAg-negative, anti-HBc positive patients receiving highly immunosuppressive regimens of extended duration. 213,214 In HBsAg-negative, anti-HBc positive subjects with moderate (\10%) or low (\1%) risk of HBV reactivation, pre-emptive therapy, not prophylaxis, is generally recommended. 205,206 The main virological event in these anti-HBc positive patients is HBsAg reappearance (seroreversion), constantly associated with hepatitis flare; by converse HBV DNA detection leads to seroreversion and hepatitis in only 50% of cases.…”
Section: -209mentioning
confidence: 99%
“…[210][211][212] Prophylaxis with ETV or TDF or TAF can be also considered in HBsAg-negative, anti-HBc positive patients receiving highly immunosuppressive regimens of extended duration. 213,214 In HBsAg-negative, anti-HBc positive subjects with moderate (\10%) or low (\1%) risk of HBV reactivation, pre-emptive therapy, not prophylaxis, is generally recommended. 205,206 The main virological event in these anti-HBc positive patients is HBsAg reappearance (seroreversion), constantly associated with hepatitis flare; by converse HBV DNA detection leads to seroreversion and hepatitis in only 50% of cases.…”
Section: -209mentioning
confidence: 99%
“…These 2 studies also showed that most HBV reactivation was observed within 1 year after completion of rituximab-containing chemotherapy, which again suggests that the monitoring of HBV DNA should be continued for at least 1 year after the completion of anti-B-cell therapy. Conversely, although antiviral prophylaxis is an alternative approach to preventing HBV reactivation in patients with resolved HBV infection, 40 there are some concerns, such as emergence of drug resistance and cost-effectiveness, that also need to be addressed. 41 …”
Section: Strategy To Prevent Hbv Reactivation In Hbsag-positive Patientsmentioning
confidence: 99%
“…Also entecavir has been proposed in the prophylaxis of reactivation of OBI. In a randomized controlled trial [89] 80 patients with CD20+ lymphoma and resolved hepatitis B were randomly assigned to a prophylactic schedule with entecavir, started before rituximab-based chemotherapy and stopped 3 mo after its discontinuation, or to be treated with entecavir once HBV reactivation and reversion to HBsAg positivity had occurred (control group). During an 18-mo follow up, HBV reactivation occurred in 2.4% of patients who underwent entecavir prophylaxis and in 17.9% of cases in the control group (P < 0.05).…”
Section: Occult Hbv Infection In Hiv-positive Subjectsmentioning
confidence: 99%